Decoupling Oxygen Tension From Retinal Vascularization as a New Perspective for Management of Retinopathy of Prematurity. New Opportunities From β-adrenoceptors - Filippi, Luca; Cammalleri, Maurizio; Amato, Rosario; Ciantelli, Massimiliano; Pini, Alessandro; Bagnoli, Paola; Dal Monte, Massimo (Frontiers in Pharmacology, 2022)
Retinopathy of prematurity (ROP) is an evolutive and potentially blinding eye disease that affects preterm newborns. Unfortunately, until now no conservative therapy of active ROP with proven efficacy is available. Although ROP is a multifactorial disease, premature exposition to oxygen concentrations higher than those intrauterine, represents the initial pathogenetic trigger. The increase of oxygenation in a retina still incompletely vascularized promotes the downregulation of proangiogenic factors and finally the interruption of vascularization (ischemic phase). However, the increasing metabolic requirement of the ischemic retina induces, over the following weeks, a progressive hypoxia that specularly increases the levels of proangiogenic factors finally leading to proliferative retinopathy (proliferative phase). Considering non-modifiable the coupling between oxygen levels and vascularization, so far, neonatologists and ophthalmologists have “played defense”, meticulously searching the minimum necessary concentration of oxygen for individual newborns, refining their diagnostic ability, adopting a careful monitoring policy, ready to decisively intervene only in a very advanced stage of disease progression. However, recent advances have demonstrated the possibility to pharmacologically modulate the relationship between oxygen and vascularization, opening thus the perspective for new therapeutic or preventive opportunities. The perspective of a shift from a defensive towards an attack strategy is now at hand.